Impoliteness strategies used in a politician’s facebook / Shamilah Abdul Halim - Abdul Halim, Shamilah (2015)
The use of computer-mediated communication particularly Facebook has become immense in our community these days. The increased online communication has also contributed to the growth of impolite language used by the participants. Thus, this study intends to firstly, investigate the types of impoliteness strategies used by facebookers in a politician’s Facebook, and secondly, to determine the factors that may contribute to impoliteness among the facebookers in computer-mediated communication (CMC), namely Facebook. 151 comments in a politician’s Facebook were analysed using Culpeper’s Impoliteness Strategies (2011) in order to identify the different strategies used by the participants. Consequently, findings showed that the most common impoliteness strategy used by Facebookers in the politician’s Facebook was insult strategy. Besides the strategies, the possible factors of impoliteness occurrences such as anonymity, lack of non-verbal cues and emotion were also determined. Due to the CMC context, these three factors contributed much to the occurrences of impoliteness in Facebook comments. Keywords: Facebook, impoliteness, computer-mediated communication